Characterization of a novel bioreactor system for 3D cellular mechanobiology studies. Issue 8 (29th February 2016) - Cook, Colin A.; Huri, Pinar Y.; Ginn, Brian P.; Gilbert‐Honick, Jordana; Somers, Sarah M.; Temple, Joshua P.; Mao, Hai‐Quan; Grayson, Warren L.
ABSTRACT: In vitro engineering systems can be powerful tools for studying tissue development in response to biophysical stimuli as well as for evaluating the functionality of engineered tissue grafts. It has been challenging, however, to develop systems that adequately integrate the application of biomimetic mechanical strain to engineered tissue with the ability to assess functional outcomes in real time. The aim of this study was to design a bioreactor system capable of real‐time conditioning (dynamic, uniaxial strain, and electrical stimulation) of centimeter‐long 3D tissue engineered constructs simultaneously with the capacity to monitor local strains. The system addresses key limitations of uniform sample loading and real‐time imaging capabilities. Our system features an electrospun fibrin scaffold, which exhibits physiologically relevant stiffness and uniaxial alignment that facilitates cell adhesion, alignment, and proliferation. We have demonstrated the capacity for directly incorporating human adipose‐derived stromal/stem cells into the fibers during the electrospinning process and subsequent culture of the cell‐seeded constructs in the bioreactor. The bioreactor facilitates accurate pre‐straining of the 3D constructs as well as the application of dynamic and static uniaxial strains while monitoring bulk construct tensions. The incorporation of fluorescent nanoparticles throughout the scaffolds enables in situ monitoring of local strain fields using fluorescent digital image correlation techniques, since the bioreactor is imaging compatible, and allows the assessment of local sample stiffness and stresses when coupled with force sensor measurements. In addition, the system is capable of measuring the electromechanical coupling of skeletal muscle explants by applying an electrical stimulus and simultaneously measuring the force of contraction. The packaging of these technologies, biomaterials, and analytical methods into a single bioreactor system has produced a powerful tool that will enable improved engineering of functional 3D ligaments, tendons, and skeletal muscles. Biotechnol. Bioeng. 2016;113: 1825–1837. © 2016 Wiley Periodicals, Inc. Abstract : A novel bioreactor and scaffolding system are presented for mechanobiology studies that enable real‐time construct conditioning and monitoring. Force sensing and fluorescent digital image correlation (FDIC) techniques enable measurements of construct contraction and local displacement, strain, and stress fields. The construct formed from bundled, aligned, electrospun fibres enhances cell growth and provides cues for elongation and alignment. The packaging of these technologies into a single system will enable improved engineering of functional tissues, particularly muscle, tendon, and ligament.